Comprehensive Appraisal of Graphene–Oxide Ratio in Porous Biopolymer Hybrids Targeting Bone-Tissue Regeneration - George Mihail Vlasceanu; Aida Șelaru; Sorina Dinescu; Cornel Balta; Hildegard Herman; Sami Gharbia; Anca Hermenean; Mariana Ionita; Marieta Costache (Nanomaterials, 2020)
The bone-tissue engineering (BTE) field is continuously growing due to a major need for bone substitutes in cases of serious traumas, when the bone tissue has reduced capacity for self-regeneration. So far, graphene oxide (GO)-reinforced natural materials provide satisfactory results for BTE, for both in vitro and in vivo conditions. In this study, we aimed to evaluate the biocompatibility of a new biocomposite consisting of chitosan and fish gelatin crosslinked with genipin and loaded with various concentrations of GO (0.5, 1, 2, 3 wt.%) for prospective BTE applications. Scaffold characterizations revealed a constant swelling degree and good resistance to enzyme degradation. The composites presented a porous structure with pores of similar size, thus mimicking the bone structure. In vitro biocompatibility assays demonstrated an overall beneficial interaction between preosteoblasts, and these particular composites, particularly with 0.5 wt.% GO, reinforced composition. Next, the materials were implanted subcutaneously in 6-week old CD1 mice for in vivo evaluation of biocompatibility and inflammatory activity. Immunohistochemical staining revealed maximal cell infiltration and minimal inflammatory reaction for fish gelatin/chitosan/genipin with 0.5 wt.% GO scaffold, thus demonstrating the best biocompatibility for this particular composition, confirming the in vitro results. This study revealed the potential use of fish gelatin/chitosan GO composites for further implementation in the BTE field.